Pengaruh Pemberian Limbah Baglog Jamur Tiram Putih (Pleurotus ostrearus) terhadap Beberapa Sifat Kimia Tanah dan Pertumbuhan Tanaman Kacang Tanah (Arachis hypogaea L.) - Wahyudi Ardi Rangga; Bambang Joko Priatmadi; Rahmi Zulhidiani (Universitas Lambung Mangkurat, 2018)
Peanut (Arachis hypogaea L.) is an important food source in Indonesia, namely as a source of vegetable protein. Then to develop the production of this plant is need for media/fertilizer that is able to deliver growth and good results. The purpose of this research is to know the influence of the granting baglog waste white Oyster Mushrooms cropping of some chemical properties of soil and growth of peanut plants. This research is the research in a pot/polybag with use (RAL) one factor, with five treatment rooms, four replicates and 20 units of the experiment. with IE giving of waste baglog white Oyster mushrooms in incubation for ± 2 weeks in soil samples, namely: K0 = 0 t ha-1 as control, K1 = 20 t ha-1 or the equivalent of 50 g, K2 = 40 t ha-1 or the equivalent of 100 g, K3 = 60 t ha-1 or the equivalent of 150 g , K4 = 80 t ha-1 or the equivalent of 200 g. Results of the research showed that giving waste white Oyster Mushrooms cropping media gives influence soil chemical properties such as: soil pH, available N-, P-available and provide high growth effect on plants , and results such as: the number of pods, and heavy seeds.